(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The strategy of poverty reductionthrough investment in education is well recognized by World Bank, AsianDevelopment Bank (ADB) and many more NGOs and Self Help Groups (SHGs) and thusa good collective start are made by all of these. This paper is an attempt tomake a strong linkage between education and poverty and to stress the need ofeducating the poor as an investment to reduce the poverty by elaborating thestart made by World Bank, Asian Development Bank and some of NGOs and Self HelpGroups. To eradicate extreme poverty and hunger is the first and foremosttarget set out in the Millennium Development Goals (MDGs) of UNESCO. To trackprogress toward this goal, it is necessary to study universal methods toeradicate poverty and adopt the best ones to achieve the MDGs. “Think about it: Every educated person is notrich, but almost every educated person has a job and a way out of poverty. Soeducation is a fundamental solution to poverty”. –Kathleen Blanco–Ex. Governor Louisiana(U.S.)